E-CULINER DESIGN DURING THE COVID-19 PANDEMIC (CASE STUDY OF CIBANTENG VILLAGE) - Marsudi, Ilham; Susetyo, Budi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The Corona virus pandemic that is happening in Indonesia and also other countries has a major impact on the economy of various sectors, especially in the culinary business sector. As if the times, technology can now help people who have culinary businesses by using applications to receive orders online or by providing culinary locations. Utilization of information technology, which is currently developing, is an appropriate strategy in order to introduce the culinary potential of a region. Designing mobile-based applications and using product and location visualizations (maps) will make it easier for people to find and reach culinary locations by utilizing Google Map technology to answer these needs. The design of E-culinary in Cibanteng Village will be realized as a Mobile application, helping to provide information on culinary places in Cibanteng Village. Besides being able to order online from this Mobile application, this application also provides information for people who have a street vendor culinary business (PKL), but only provides place information for street vendors, does not accept delivery messages.